Peran Pendidik dalam Meningkatkan Kecerdasan Sosial Emosional pada Anak Usia Dini di RA Darul Fatihin NW Gerintuk: The Role of Educators in Improving Social-Emotional Intelligence in Early Childhood at RA Darul Fatihin NW Gerintuk - Ahmad Izzudin (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
Education is an important aspect for the development of human resources, because education is one of the methods used to improve human quality. This research aims to determine the role of educators in providing stimulation to increase children's social emotional intelligence and determine the forms of stimulus provided by educators in increasing children's social emotional intelligence at RA Darul Fatihin NW Gerintuk. The method used in this research is a qualitative method with a descriptive approach. The results of research regarding the role of educators in improving social emotional intelligence in early childhood at RA Darul Fatihin NW Gerintuk are that teachers are able to act as parents for students when children are in a school environment with full supervision, reprimand with affectionate reprimands, prioritize instilling religious values, get used to behaving well with polite words in interactions that rely on essential needs so that children can understand them, and teachers are able to develop learning strategies that can increase social emotional intelligence with a form of stimulation, namely development. cognitive, motor development, effective at school.